Implementation of Rasch Model for Mapping Students’ Metacognitive Awareness - Sukarelawan, M I; Jumadi, J; Kuswanto, H; Nurjannah, T; Hikmah, F N; Ramadhan, M F (Department of Physics, Faculty of Mathematics and Natural Sciences, 2021)
This study aim is to map students’ metacognitive awareness in physics subjects. This research was conducted at SMAN 1 Bantarsari in 2020. A total of 112 respondents (male = 17% and female = 83%) from class XI and XII were selected using a combination of snowball techniques and convenience sampling. Students’ metacognitive physics awareness was administrated using the Physics Metacognition Inventory (PMI) and analyzed using the Rasch model. The PMI inventory consists of 26 items and uses a Likert scale of 5 ratings ranging from 1 (never) to 5 (always). Mapping students’ physics metacognitive awareness based on the Logit Value of Person. Metacognitive awareness is classified into four levels, namely: low, medium, high, and very high levels. The results showed that more than 80% of students had metacognitive awareness at moderate and high levels. Dominant female students have metacognitive awareness at a high level and male students at a moderate level. The students’ metacognitive awareness in class XI and XII were at very high and moderate levels, respectively. The 15-16 year age group was dominant at a moderate level and the 17-18 year age group at a high level.